2020
DOI: 10.1002/mus.27038
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in chronic inflammatory demyelinating polyneuropathy

Abstract: Introduction: In this study we aimed to better understand fatigue in chronic inflammatory demyelinating polyneuropathy (CIDP) as it relates to disease activity status. Methods: Patients with probable or definite CIDP were stratified into active CIDP or CIDP in remission. Assessments of fatigue, physical impairment, disability, sleepiness, sleep quality, and depression were collected. Results: Of the 85 patients included in the study, 46 (54%) had active disease, whereas 39 (46%) were in remission. Fatigue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…A considerable number of patients reported neuropathic pain and nearly all patients reported fatigue interfering with daily activities. Both fatigue and pain are common (long-term) symptoms and can persist despite treatment [40][41][42][43]. The reported median fatigue scores in our study are comparable to other data in the literature and considerably higher than median scores derived from control populations as reported in other studies [41,42].…”
Section: Discussionsupporting
confidence: 84%
“…A considerable number of patients reported neuropathic pain and nearly all patients reported fatigue interfering with daily activities. Both fatigue and pain are common (long-term) symptoms and can persist despite treatment [40][41][42][43]. The reported median fatigue scores in our study are comparable to other data in the literature and considerably higher than median scores derived from control populations as reported in other studies [41,42].…”
Section: Discussionsupporting
confidence: 84%
“…As above, fatigue is a non‐specific symptom and seen in many diseases. Furthermore, fatigue is seen in both active CIDP and CIDP in remission as shown by Gable and colleagues 14 . They concluded that fatigue is likely a residual symptom that does not require immune therapy.…”
mentioning
confidence: 87%
“…6,13,14 Thus, one must conclude that fatigue can be improved by treatment of the underlying condition only to a minor degree. 10,14 There are studies that exercise may improve fatigue in most chronic disorders, but prospective, randomized studies are necessary to confirm this in CIDP. 8,11,12 Many other items that are related to and impact fatigue but are not specific to the disease in question are known, including age, gender, obstructive sleep apnea, poor sleep, depression, anxiety, personality type, and life experiences.…”
mentioning
confidence: 99%
See 2 more Smart Citations